A perícia de incêndio no processo de melhoria contínua do sistema de segurança contra incêndio - Lugon, André Pimentel (2019)
In the face of the national economic crisis, public services are increasingly in need of quality. For this, their processes must be efficient and constantly improved in order to meet the demands of society. In Espírito Santo, constitutionally, the Military Fire Corps is responsible for the actions of Fire Safety (SCI), with the competence to create norms of prevention, to supervise its execution, to attend emergencies involving fires, as well as to investigate them or periciate them. Through the fire investigation activity is possible to understand the phenomena related to the fire and to detect the inconsistencies in the processes related to SCI and to correct them, promoting their improvement. It is observed that over the years the fire investigation of the Military Fire Corps has disconnected from the objective of providing the managers of these corporations with information that provides actions for the continuous improvement of the systems related to SCI, prioritizing, due to structural and circumstantial issues, judicial and civil lawsuits. The achievement of a good fire investigation, without commitment to the processes related to SCI, is not enough to contribute to the continuous improvement of this system. The present research is a dissertation of the Master Course in Public Management, whose subject is the fire investigation in the process of continuous improvement of the fire safety system. The objective of the work was to propose actions for the improvement of the structure and processes related to the activity of fire investigation for the continuous improvement of the SCI system (SISCI). In order to achieve this objective, it was necessary to explain the concepts related to continuous improvement, the PDCA cycle and its applications in public management, describe the stages of the SCI operational cycle, the processes related to the fire investigation activity and relate them to the SISCI in the Espírito Santo. In addition, seventy fire reports were analyzed and and questionnaires were applied to military firefighters who act as fire investigators. With this, it was possible, based on the results found, to propose actions for the improvement of the fire investigation activity and that will contribute to the continuous improvement of the Fire Safety System in the ES: restructuring of the fire department, requalification plan of fire investigator, seminar of good practices, implementation of the fixed scale and partnerships with research centers